2015
DOI: 10.2967/jnumed.115.158121
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Radiation Injury and Recovery in Bone Marrow Using 18F-FLT PET/CT and USPIO MRI in a Rat Model

Abstract: We present and test the use of multimodality imaging as a topological tool to map the amount of the body exposed to ionizing radiation and the location of exposure, which are important indicators of survival and recovery. To achieve our goal, PET/CT imaging with 3′-deoxy-3′-18 Ffluorothymidine ( 18 F-FLT) was used to measure cellular proliferation in bone marrow (BM), whereas MRI using ultra-small superparamagnetic iron oxide (USPIO) particles provided noninvasive information on radiationinduced vascular damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…IR induces a huge decrease of nucleated cells in bone marrow and repression of hematopoiesis [25,26]. We found that HKMT protected bone marrow structure and restored the number of nucleated cells.…”
Section: Hkmt Inhibited Radiation Injuries On Testis Tissuesmentioning
confidence: 76%
“…IR induces a huge decrease of nucleated cells in bone marrow and repression of hematopoiesis [25,26]. We found that HKMT protected bone marrow structure and restored the number of nucleated cells.…”
Section: Hkmt Inhibited Radiation Injuries On Testis Tissuesmentioning
confidence: 76%
“…Preservation of bone marrow has been shown to increase survival rates after radiation exposure at doses that are within the range of the gastrointestinal syndrome (7.5 Gy in rats) [12, 25, 43] and the role of bone marrow in the recovery of the gastrointestinal syndrome have been studied and established through many studies [12, 43]. By affecting survival, partial shielding can mask the effect of the gastrointestinal syndrome, which renders our imaging observations of both bone marrow and gastrointestinal signals ever more important.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue uptake is measured using standardized uptake value normalized to body weight (SUV) or radioactivity activity concentration over amount injected normalized by body weight of the animal. Bone marrow ROIs were selected using the spatial information from the CT scan and an algorithm developed in-house, the details of our method has been previously published [25]. Briefly, a mask was generated corresponding to the bone structures from the CT scan and applied to the PET data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR induced severe injuries in hematopoietic tissue which may lead to death [15, 16]. G-CSF and IL-6 are critical in hematopoiesis [17-20].…”
Section: Discussionmentioning
confidence: 99%